PERAN PROFITABILITAS DAN LIKUIDITAS TERHADAP ISLAMIC SOCIAL REPORTING - Sulfati, Andi (Jurnal Unicorn ADPERTISI, 2023)
The purpose of this study is to examine the influence of profitability on Islamic Corporate Social Responsibility(ICSR) and to examine the influence of liquidity on Islamic Corporate Social Responsibility (ICSR). This studyis a quantitative research method with a multiple regression method, and the sample subjects are 19 companyfinancial statements in JII during 2019-2022. Companies listed on JII are public companies, which means thatthe company has offered public offerings to the public and has been listed on the stock exchange. The researchuses the latest year because in this era it has developed and advanced in terms of sharia stocks and can provideinformation to the public on the results of this research. By using classical assumption test analysis tools includingnormality and multicollinearity tests and using the T (partial) test and determination coefficient for thehypothesis test. profitability has a positive and significant effect on Islamic Corporate Social Responsibility(ICSR), then liquidity has a positive and significant effect on Islamic Corporate Social Responsibility (ICSR).